The Effects of Oral Application of Cyromazine and Triflumuron on House-Fly Larvae - B Vazirianzadeh; MA Jervis; NAC Kidd (Tehran University of Medical Sciences, 2007)
Accumulations of large quantities of wastes (manure, used litter, dead birds) which are excellent medium for fly-larvae over poultry houses provide breeding places for different groups of fly pests, with house-flies being the dominant species. This project is a comparative lab study. In this research project the larvicidal effects of cyromazine and triflumuron were studied as two Insect Growth Regulators (IGRs) to reduce the fly population using oral application. Both IGRs had a signifi-cant effect on larval mortality compared with their controls among the concentrations (P< 0.01, Fisher's LSD with Bonf-feroni correction) including a dose-dependent relationship. Comparisons among LC50 and LC90 values, using fiducial limits, showed that cyromazine was significantly more toxic to the larvae of the two strains than triflumuron. It is concluded that cyromazine should be used in a larvicidal programme to control house-fly rather than triflumuron.